Potret kemampuan penalaran spasial serta persepsi siswa sekolah menengah pertama terhadap geometri dan matematika - Fitriyani, Harina; Kusumah, Yaya Sukjaya; Dahlan, Jarnawi Afgani; Hendroanto, Aan (Universitas PGRI Semarang, 2025)
Geometry is a field of mathematical study closely related to spatial reasoning and its many uses in everyday life. The purpose of this study was to photograph the spatial reasoning ability of junior high school students in doing spatial tasks from a gender perspective and their perceptions of the geometry material and mathematics. A qualitative approach was chosen to describe the research findings. One hundred two junior high school students in Sleman Yogyakarta participated in spatial reasoning tests, interviews, and questionnaires. Data analysis uses data reduction, data presentation, and verification stages. The results showed that the average student's spatial reasoning ability was still low, 42.09. Most students mastered spatial tasks in spatial orientation, while the students' mastery of spatial reasoning was the weakest in the element of spatial visualization. From a gender perspective, male students showed superior spatial reasoning abilities than female students. Students perceive mathematics and geometry as complex materials, but they are essential to learning because of their many benefits in everyday life.